2004
DOI: 10.1254/jphs.95.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of K+ Channels Modulators Terikalant and Glibenclamide on Membrane Potential Changes Induced by Hypotonic Challenge of Guinea Pig Ventricular Myocytes

Abstract: Abstract. Contribution of inward rectifier K+ currents (I K1 ) and ATP-sensitive K + currents (I KATP ) to membrane potential changes of ventricular myocytes appearing during hypotonic challenge is unclear. We used here the whole cell patch clamp technique, voltage and current clamp modes, to record membrane potentials and ionic currents in isolated guinea pig ventricular myocytes under isotonic or hypotonic perfusion. The difference in osmolarity between isoand hypotonic solutions was about 100 mOsm. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…On the other hand, hypo-osmotic stress increased efficacy of K + -channel opening drugs to activate I K,ATP in guinea-pig ventricular myocytes (Kocic et al 2007). These findings by Kocic et al (2004a; are in agreement with our observations of rat ventricular myocytes in terms of (1) lack…”
Section: Mitsuyama Et Al Page 15supporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, hypo-osmotic stress increased efficacy of K + -channel opening drugs to activate I K,ATP in guinea-pig ventricular myocytes (Kocic et al 2007). These findings by Kocic et al (2004a; are in agreement with our observations of rat ventricular myocytes in terms of (1) lack…”
Section: Mitsuyama Et Al Page 15supporting
confidence: 93%
“…This abbreviation of APD was associated with appearance of outward currents that were inhibited by glibenclamide, a blocker of K ATP channels (Priebe and Beuckelmann 1998). In contrast, it was reported that, using terikalant (a blocker of inward rectifier K + currents (I K1 )) and glibenclamide, neither I K1 nor I K,ATP participated in membrane potential changes induced by hypo-osmotic solution at least with sufficient intracellular ATP (Kocic et al 2004a). On the other hand, hypo-osmotic stress increased efficacy of K + -channel opening drugs to activate I K,ATP in guinea-pig ventricular myocytes (Kocic et al 2007).…”
Section: Mitsuyama Et Al Page 15mentioning
confidence: 97%
See 1 more Smart Citation
“…The functional implication of disparate structure of atrial and ventricular K ATP is unclear, but conceivably, SUR1-based channels are necessary for an atrial specific function, such as coupling atrial stretch with the secretion of atrial natriuretic peptide (186, 206, 348, 441). Interestingly, atrial K ATP channels have been reported to be activated by stretch (214, 326, 416), although the data is sparse, and the finding that atrial Kir3.4 channels are also stretch-sensitive (173) may provide an alternative explanation.…”
Section: B Katp In Cardiac Musclementioning
confidence: 99%
“…Some authors claimed that I KATP are activated during cell swelling, but only at low concentration of ATP in the cell [44,45]. On the other hand, in the presence of 5 mM of ATP in the pipette solution, no I KATP was detected during hypotonic swelling of guinea pig ventricular myocytes [13,46]. But, it is clear that neither activation nor inhibition of these channels has significant influence on the cardiac cell volume.…”
Section: Atp-sensitive K + Channels (I Katp )mentioning
confidence: 99%